Cryo-XPS study of xanthate adsorption on pyrite - Deng, Meijiao; Karpuzov, Dimitre; Liu, Qingxia; Xu, Zhenghe (Surface and interface analysis, 2013)
The adsorption of xanthate on pyrite has been extensively studied. However, the adsorption mechanisms remain a subject of controversy. Formation of both dixanthogen and metal‐xanthate complexes has been suggested. In this study, both room temperature X‐ray photoelectron spectroscopy (XPS) (RT‐XPS) and liquid nitrogen temperature XPS (Cryo‐XPS) were used to study interactions between pyrite and xanthate. While dixanthogen was not detected by RT‐XPS, it was successfully identified through C1s and S 2p peaks using Cryo‐XPS. The impact of pH and copper activation on adsorption of xanthate on pyrite was also investigated. It was found that at low pH, dixanthogen is the dominant species of xanthate adsorption on pyrite. At high pH, metal‐xanthate complexes were found to be prevalent on pyrite surfaces, which are responsible for the surface hydrophobicity. Copper activation showed a significant effect on xanthate adsorption on Cu‐activated pyrite, resulting in mostly the formation of Cu‐xanthate complexes rather than dixanthogen, mainly in the form of Cu(I)‐isopropyl xanthate complex (CuIPX). Copyright © 2012 John Wiley & Sons, Ltd.